Historical biological essentialism. (October 2018) - Devitt, Michael
Highlights: Historical explanation demands an historical component to a taxon's essence. The historical component is not descent from certain particular organisms. Nor descent from a certain wholly relational kind of organism. It is descent from a kind with a certain intrinsic component to its essence.